Optimization of the Statin Therapy Algorithm in Outpatient Practice: Adherence and Economic Benefits - S. A. Davitashvili; D. V. Nebieridze; N. M. Akhmedzhanov; A. S. Lishuta; A. S. Safaryan (Рациональная фармакотерапия в кардиологии)
Aim. To study adherence to recommended treatment, additional clinical and economic benefits of a titration-free statin therapy regimen.Material and methods. Ambulatory patients (n=300) with a high or very high risk of hypercholesterolemia who have indications for statin treatment for primary or secondary prevention of cardiovascular diseases is included in a non-randomized trial. Patients are divided into 2 groups. Group 1 had a titration regimen of statins in accordance with current recommendations (group 1A [n=50] – primary cardiovascular prevention; group 1B [n=100] – secondary cardiovascular prevention). Group 2 received a titration-free statin regimen in fixed doses (group 2A [n=50] – primary cardiovascular prevention; group 2B [n=100] – secondary cardiovascular prevention). Patients were prescribed atorvastatin (10-80 mg/day) or rosuvastatin (10- 40 mg/day). Group 1 patients had visits to the doctor after 1, 3, 6 and 12 months from the start of statin use, group 2 patients after 3 and 12 months. Treatment adherence, effects on surrogate and hard endpoints, and cost-effectiveness of the two statin regimens were evaluated.Results. The target level of low-density lipoprotein cholesterol (LDL-C) after 12 months in group 2 was achieved in 56.4% of patients versus 53.4% in group 1. The average level of LDL-C decreased by 1.84±0.44 mmol / l in group 2 versus a decrease of 1.61±0.47 mmol / L in group 1. The costeffectiveness ratio was 9658.72 rubles in group 2 versus 8341.73 rubles in group 1 for a 1 mmol / l LDL-C level decrease in 1 patient within a year. An increase in annual costs per patient in group 2 compared with group 1 by 75.76 rubles reduced the relative risk of developing a combined endpoint by 1% per year.Conclusion. The use of a titration-free statin treatment regimen allowed us not only to more effectively control of LDL-c levels in patients with high and very high cardiovascular risk compared to the traditional statin therapy regimen, but also to obtain economic advantages in patients with high and very high cardiovascular risk.